The Effects of β -Glucans on Dendritic Cells and Implications for Cancer Therapy - Albeituni, Sabrin H.; Yan, Jun (Anti-Cancer Agents in Medicinal Chemistry, 2013)
β-Glucans are polysaccharides of β-D-glucose extracted from the cell walls of different species of mushrooms, yeast, oat, barley, seaweeds, algae and bacteria. Modern biomedical research has identified β-glucans as biological response modifiers (BRM) with anti-tumor properties that elicit potent immune responses through their recognition by a variety of pattern recognition receptors (PRRs) on dendritic cells (DCs), macrophages and neutrophils. Complement receptor-3 (CR3), lactosylceramides, scavenger receptors and dectin-1 are involved in β-glucan recognition, triggering a series of signaling events that modulate innate and subsequently adaptive immune responses. β-Glucan binding to specific receptors in DCs and macrophages triggers their activation and maturation, increases their antigen-presentation ability and enhances the production of proinflammatory cytokines that stimulate the polarization of TH1 or TH17 responses, and induces the activation of antigen-specific CD8+ cytotoxic T lymphocytes (CTL). Moreover, large β-glucans can be degraded by macrophages into smaller moieties, when released, prime CR3 receptor on neutrophils and natural killer (NK) cells mediating CR3-dependent cellular cytotoxicity (CR3-DCC) of iC3b opsonized tumor cells. Elucidating the molecular mechanisms of β- glucan-induced signaling in immune cells is essential for the design of new therapeutic strategies against cancer. Future studies should be done to translate β-glucan research to the clinic.
Keywords: dendritic cells (DC)